From research application to research output: an overview of best practice to facilitate timely access to data. - SRS Project and Statistical Support Team (International Journal of Population Data Science, 2025)
Objectives Through this presentation, researchers will be taught and equipped with the essential skills they need to produce research applications which are high quality. Researchers will also learn how to produce high quality statistical outputs which deliver benefits for the public good. Method In this presentation we will cover the five safes framework. This framework is essential in the process of accessing data and underpins all research which is facilitated through the Secure Research Service (SRS). Through this presentation we will assess the common challenges researchers face when completing an application and delivering outputs and how these can be overcome. We will also comprehensively cover the various roles of stakeholders involved in the process of accessing an application and output, and the requirements they may have. Results Through this session we hope to ensure researchers have the practical skills they need to deliver a high quality application and subsequent statistical outputs. This will enable the operational teams in the Secure Research Service (SRS) to understand applications, researchers intentions and requirements and therefore process requests in as timely manner as possible. Overall this will enable researchers to publish their results quicker. Conclusion Through understanding what makes a great research application and output, researchers will be able to take away key transferable skills which can be used for all future research projects.